2019
DOI: 10.7150/jca.32608
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of cancer cells with chemotherapeutic drugs results in profound changes in expression of genes encoding aldehyde-metabolizing enzymes

Abstract: Using RNA-seq, RT-qPCR, and bioinformatics we have studied the influence of a wide spectrum of chemotherapeutic drugs on transcription of AKR1B10 , AKR1C1 , ALDH1A1 , and ALDH1A3 genes, which encode the major aldehyde-metabolizing enzymes. The strongest alterations were detected in case of AKR1B10 mRNA that was significantly upregulated in wild type p53 cancer cells, but downregulated in mutant p53 cancer cells. Subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
(32 reference statements)
1
8
0
Order By: Relevance
“…Although initially surprising, the reduced expression of AKR1B10 in the tumours is consistent with the previously reported decreased AKR1B10 expression in human colorectal cancer [37,38] and the decrease in the mRNA levels for AKR1B10 in sera of colon cancer patients in comparison with sera of healthy donors [39]. In addition to Nrf2, AKR1B10 is transcriptionally regulated by p53 [37,40], in agreement with the upregulation of the AKR1B10 mRNA by chemotherapeutic agents in normal diploid cells and in cancer cells expressing wild type p53, and its downregulation in cancer cells harbouring mutant p53 [39]. Because p53 is commonly mutated in colorectal cancer [41], the observed downregulation of AKR1B10 in our study is most likely due to loss of the normal function of p53.…”
Section: Discussionsupporting
confidence: 89%
“…Although initially surprising, the reduced expression of AKR1B10 in the tumours is consistent with the previously reported decreased AKR1B10 expression in human colorectal cancer [37,38] and the decrease in the mRNA levels for AKR1B10 in sera of colon cancer patients in comparison with sera of healthy donors [39]. In addition to Nrf2, AKR1B10 is transcriptionally regulated by p53 [37,40], in agreement with the upregulation of the AKR1B10 mRNA by chemotherapeutic agents in normal diploid cells and in cancer cells expressing wild type p53, and its downregulation in cancer cells harbouring mutant p53 [39]. Because p53 is commonly mutated in colorectal cancer [41], the observed downregulation of AKR1B10 in our study is most likely due to loss of the normal function of p53.…”
Section: Discussionsupporting
confidence: 89%
“…Most of the agents upregulate AKR1B10, whereas a phorbol ester 12- O -tetradecanoylphorbol 13-acetate (TPA) down-regulates the expression [ 15 ]. 5-Fluorouracil (5-FU) and oxaliplatin (L-OHP) exhibit opposite effects on the AKR1B10 expression depending on colorectal cancer (CRC) cell lines [ 16 ]. Regulators and signal molecules involved in the modulation of AKR1B10 expression by several agents are also listed in Table 1 .…”
Section: Gene Regulation Of Akr1b10mentioning
confidence: 99%
“…Alternatively, expression was induced by these agents in c CRC HCT116 cells having wild-type p53. When the p53 gene in HCT116 cells is knocked-down, 5-FU can no longer induce AKR1B10 [ 16 ]. Thus, p53 protein might act as a switch to determine the direction of AKR1B10 expression, suggesting that the level and status of p53 might be an important factor.…”
Section: Gene Regulation Of Akr1b10mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have confirmed the critical role of ALDH1A3 in increasing metastatic behavior and cancer stemness in several cancer types, including breast cancer, lung cancer, colon cancer, glioblastoma, and cholangiocarcinoma [ 16 , 21 , 22 , 23 , 24 , 25 , 26 ]. Kim et al reported that the activation of hypoxia-inducible factor-2α enhances breast cancer stemness [ 22 ].…”
Section: Discussionmentioning
confidence: 99%